2021 Electricity Profiles - United Nations Department of Economic; Social Affairs (United Nations, 2024)
The 2021 Electricity Profiles contains electricity profiles for about 225 countries and territories, providing detailed information on production, trade and consumption of electricity, net installed capacity and thermal power plant input and efficiency for all countries. Electricity production and electric installed capacity are disaggregated by source, as coming from combustible fuels, hydro, nuclear and other sources; and by type of producer, whether from main activity producers or auto producers.